1998
DOI: 10.1128/jvi.72.6.4552-4559.1998
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Determinants for Envelope Binding and Infection in Tva, the Subgroup A Avian Sarcoma and Leukosis Virus Receptor

Abstract: Tva is the cellular receptor for subgroup A avian leukosis and sarcoma virus (ALSV-A). The viral interaction domain of Tva is determined by a 40-residue, cysteine-rich module closely related to the ligand binding domain of the human low-density lipoprotein receptor (LDLR). In this report, we examined the role of the LDLR-like module of Tva in envelope binding and viral infection by mutational analysis. We found that the entire LDLR module in Tva is essential for efficient binding to the viral envelope protein.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 23 publications
(52 reference statements)
0
27
0
Order By: Relevance
“…Initial characterization of the extracellular domain of the quail Tva receptor showed that the principal domains of Tva required for efficient binding to the ALV(A) envelope glycoproteins and infection of cells expressing Tva are contained within the extracellular region of Tva homologous to the LDLR cysteine-rich ligand binding domain (51,71). Further characterization of the quail Tva receptor revealed that the carboxy-terminal half of the LDLR motif was required for receptor function (53,54,72). The overall structure of the Tva cysteine-rich region (amino acids 11 to 50 in quail Tva) is formed by three disulfide bonds (C1-C3, C2-C5, and C4-C6) between the six cysteine residues (Cys-11, Cys-18, Cys-28, Cys-35, Cys-41, and Cys-50) ( Fig.…”
mentioning
confidence: 99%
“…Initial characterization of the extracellular domain of the quail Tva receptor showed that the principal domains of Tva required for efficient binding to the ALV(A) envelope glycoproteins and infection of cells expressing Tva are contained within the extracellular region of Tva homologous to the LDLR cysteine-rich ligand binding domain (51,71). Further characterization of the quail Tva receptor revealed that the carboxy-terminal half of the LDLR motif was required for receptor function (53,54,72). The overall structure of the Tva cysteine-rich region (amino acids 11 to 50 in quail Tva) is formed by three disulfide bonds (C1-C3, C2-C5, and C4-C6) between the six cysteine residues (Cys-11, Cys-18, Cys-28, Cys-35, Cys-41, and Cys-50) ( Fig.…”
mentioning
confidence: 99%
“…The LDL-A module in Tva, when appended to a heterologous membrane anchor, is sufficient to mediate ASLV(A) entry (51). Mutations within the LDL-A module severely affect subgroup A envelope (EnvA) binding and virus entry, which suggests that the envelope binding site is composed of discontinuous regions within the LDL-A module (8,54,74,75). Recent work demonstrates that three amino acid substitutions in the hLDLR module A4 convert this module into an ASLV(A) receptor (53).…”
mentioning
confidence: 99%
“…To ensure that the receptor protein incorporated into the virus was responsible for the infectivity of the pseudotypes, we produced virions carrying a nonfunctional mutant of Tva (Tva*). This receptor mutant contains five amino acid substitutions that abrogate its ability to bind envelope or facilitate EnvA-mediated infection of target cells (31). Western blot analysis of virions produced by transient transfection revealed that Tva* was incorporated into MLV pseudotypes at a level which was very similar to that of wild-type Tva; however, the MLV(Tva*) virions were unable to infect 3T3EnvA cells (data not shown).…”
Section: Incorporation Of Tva Into MLV Virionsmentioning
confidence: 97%